Long‐Term Measurements Show Little Evidence for Large Increases in Total U.S. Methane Emissions Over the Past Decade. Issue 9 (15th May 2019) - Lan, Xin; Tans, Pieter; Sweeney, Colm; Andrews, Arlyn; Dlugokencky, Edward; Schwietzke, Stefan; Kofler, Jonathan; McKain, Kathryn; Thoning, Kirk; Crotwell, Molly; Montzka, Stephen; Miller, Benjamin R.; et al.
Abstract: Recent studies show conflicting estimates of trends in methane (CH4 ) emissions from oil and natural gas (ONG) operations in the United States. We analyze atmospheric CH4 measurements from 20 North American sites in the National Oceanic and Atmospheric Administration Global Greenhouse Gas Reference Network and determined trends for 2006–2015. Using CH4 vertical gradients as an indicator of regional surface emissions, we find no significant increase in emissions at most sites and modest increases at three sites heavily influenced by ONG activities. Our estimated increases in North American ONG CH4 emissions (on average approximately 3.4 ± 1.4 %/year for 2006–2015, ±σ) are much smaller than estimates from some previous studies and below our detection threshold for total emissions increases at the east coast sites that are sensitive to U.S. outflows. We also find an increasing trend in ethane/methane emission ratios, which has resulted in major overestimation of oil and gas emissions trends in some previous studies. Plain Language Summary: In the past decade, natural gas production in the United States has increased by 46%. Methane emissions associated with oil and natural gas productions have raised concerns since methane is a potent greenhouse gas with the second largest influence on global warming. Recent studies show conflicting results regarding whether methane emissions from oil and gas operations have been increased in the United States. Based on long‐term and well‐calibrated measurements, we find that (i) there is no large increase of total methane emissions in the United States in the past decade; (ii) there is a modest increase in oil and gas methane emissions, but this increase is much lower than some previous studies suggest; and (iii) the assumption of a time‐constant relationship between methane and ethane emissions has resulted in major overestimation of an oil and gas emissions trend in some previous studies. Key Points: Long‐term measurements show no large increases in U.S. methane emissions in the past decade The estimated increase in U.S. oil and natural gas CH4 emissions is an order of magnitude lower than some previous studies The increasing trend in C2 H6 /CH4 emission ratios has resulted in major overestimation of an oil and gas emissions trend in some previous studies